Middle East and North Africa Economic Monitor, October 2016 Economic and Social Inclusion to Prevent Violent Extremism - Devarajan, Shantayanan (Middle East and North Africa Economic Monitor, 2016)
The year 2016 appears to be one of the toughest for the Middle East and North Africa (MENA) region as their governments face serious policy challenges. The biggest challenge for oil exporters is managing their finances and diversification strategies with oil below